Is disability exclusion associated with experiencing an unmet need for health care?. (5th December 2019) - Temple, Jeromey B.; Stiles, Jay A.; Utomo, Ariane; Kelaher, Margaret; Williams, Ruth
Abstract: Objective: To examine the association between disability exclusion and experiencing an unmet need for health care. Methods: The 2015 Survey of Disability Ageing and Carers was used to measure the prevalence of unmet needs for health care stratified by measures of exclusion. Log‐Poisson models were fitted to examine the association between discrimination, avoidance and unmet needs for health care. Results: Approximately 10% of respondents reported an unmet need to attend a GP, specialist or hospital and 25% reported an unmet need to obtain dental treatment. For those reporting an instance of discrimination in the last 12 months, the rates of experiencing unmet needs for health care were significantly higher (GP 29%, specialist 26%, dental 46%, hospital 18%). With controls included, discrimination or avoidance significantly increased the probability of reporting an unmet need for health care regardless of the context of previous experiences of exclusion. Conclusion: Disability discrimination or avoidance is strongly associated with experiencing an unmet need for health care among older people with disabilities.